2017
DOI: 10.1016/j.jnucmat.2017.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laser shock peening on irradiation defects in austenitic stainless steels

Abstract: The laser shock peening process can generate a dislocation network, stacking faults, and deformation twins in the near surface of austenitic stainless steels by the interaction of laserdriven shock waves with metals. In-situ transmission electron microscopy (TEM) irradiation studies suggest that these dislocations and incoherent twin boundaries can serve as effective sinks for the annihilation of irradiation defects. As a result, the irradiation resistance is improved as the density of irradiation defects in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The improvement in mechanical and corrosion properties such as hardness, fatigue strength, stress corrosion cracking, and hydrogen embrittlement by LSP have been well documented in the literature . Recently, it is reported by our team that the microstructural changes by LSP are beneficial for improving the radiation resistance of austenitic stainless steels . The dislocations and incoherent twin boundaries can serve as high strength sinks for the annihilation of irradiation defects during 1 MeV Kr ion irradiation at room temperature.…”
Section: Introductionmentioning
confidence: 89%
“…The improvement in mechanical and corrosion properties such as hardness, fatigue strength, stress corrosion cracking, and hydrogen embrittlement by LSP have been well documented in the literature . Recently, it is reported by our team that the microstructural changes by LSP are beneficial for improving the radiation resistance of austenitic stainless steels . The dislocations and incoherent twin boundaries can serve as high strength sinks for the annihilation of irradiation defects during 1 MeV Kr ion irradiation at room temperature.…”
Section: Introductionmentioning
confidence: 89%
“…Especially in nuclear reactors, metals used in reactor cores need to perform optimally in at elevated temperature range of 300-350 °C as well as in aqueous environments. The conditions inside a nuclear reactor may lead to corrosion or stress corrosion cracking (SCC), radiation hardening [2], radiation defects and radiation embrittlement or helium embrittlement of the metals. Therefore it is essential and advisable to use materials which can withstand those conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Sano et al [6] utilized the second harmonic laser for underwater nuclear power plant maintenance applications, and their research explained that LSPwC could induce compressive residual stress on the surface and prompts to the aversion of SCC start and enhancement of fatigue strength. Q. Lu et al [2] performed laser shock peening (LSP) on 304 austenitic stainless steel and unveiled that the dislocation sinks created due to LSP process help in improving radiation resistance and lowering the radiation defect densities at room temperature (25 °C) and as well as at 300 °C. Peyre et al [8] carried out LSP on 316L austenitic stainless steel and revealed the post beneficial effects of LSP on its pitting corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The images of the hexagonal structures in Figure 7 indicates the process of squeezing, bending, and extending the copper foil in laser shock forming. The plastic deformation of copper foil is equivalent to being rolled in an ultrashort time, which makes the copper work harden [19,20].…”
Section: The Analysis Of Mechanical Properties and Laser Shock Forming Mechanism Of Copper Foilmentioning
confidence: 99%